Single-component conformal material as well as preparation method, application and application method thereof

By using high-temperature resistant resin and physical crosslinking agent in the cladding material to form a single-component cladding material, multiple problems in the production and construction of the cladding material in the prior art are solved, efficient environmental barriers and high-temperature resistance are achieved, and internal stress is reduced, which is suitable for a variety of substrates and workpieces.

CN119614075APending Publication Date: 2025-03-14LIAONING SILICATE RES INST

Patent Information

Application Number
CN202510163260.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

During the production and construction of existing covering materials, there are problems such as complex composition, complex curing process, changes in appearance and dimensions after curing, damage to workpieces due to internal stress and strain, poor temperature resistance and environmental barrier performance after curing, and release of harmful substances after performance decay.

Method used

A single component covering material is provided, including a high temperature resistant resin and a physical crosslinking agent. Through the combination of the physical crosslinking agent and the high temperature resistant resin, a covered surface protective film material with good heat resistance, hydrophobic and environmental barrier properties is formed, and the interior has a lower internal stress during the curing process and after the curing is completed.

Benefits of technology

It has achieved the formation of a cover surface protective film material with special functions such as high temperature resistance, hydrophobicity, and environmental barriers on the surfaces of various substrates, and has low internal stress, which is suitable for environmental protection on the surface of workpieces with fine structures, and extends the environmental protection effect of the base coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of conformal materials, and particularly provides a single-component conformal material as well as a preparation method, application and an application method.The single-component conformal material comprises high-temperature-resistant resin and a physical cross-linking agent, the high-temperature-resistant resin is one or more of high-temperature-resistant resin meeting the chemical formula A or one or more of emulsions formed by the high-temperature-resistant resin meeting the chemical formula A. The single-component conformal material provided by the invention is a conformal material which is used in a single-component form and has certain surface hydrophobicity, has high temperature resistance, good environment barrier capability and relatively high insulation and corrosion resistance, is an organic silicon-based conformal material with certain surface environment protection performance, and has a good application prospect. While maintaining a good environmental protection effect, the coating has good construction characteristics, and is suitable for protection of surfaces of various base materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coating materials, and specifically provides a single-component coating material and a preparation method, application and application method. The single-component coating material is a coating material used in a single-component form and having a certain hydrophobic property on the surface. It has high temperature resistance, good environmental barrier capability, high insulation and corrosion resistance. It is a silicone-based coating material with certain surface environmental protection performance. While maintaining a good environmental protection effect, it also has good construction characteristics and is suitable for the protection of various substrate surfaces. Background Art

[0002] Existing surface protection and environmental shielding materials are of various types, widely used, and have mature technologies. However, due to the limitations of existing material technology, the inventors found during the production and construction process that the existing technology has several key problems from the perspective of molding and application. These mainly include: the ingredients are complex, unstable, and mostly toxic; the curing process is complicated or requires additional equipment or process steps; the external dimensions change significantly after curing; large stresses and strains are generated inside the material during the curing process, causing damage to some workpieces with fine surface structures; they cannot be easily removed after curing; the heat resistance is poor after curing; the environmental barrier performance is poor after curing; and the harmful substances are continuously released into the environment as the performance decays after curing, etc. In some cases, practitioners of conformal materials have to increase the dosage or film thickness to meet the requirements of environmental protection indicators, or fundamentally change the design of the workpiece or reduce the design life of the workpiece to cope with the current situation of insufficient performance of existing conformal materials.

[0003] The adhesives or coating materials disclosed in Chinese patents CN102559047B, CN101805562B, CN110628326A, CN108913089B, CN103666250B, CN112680176A, CN103613931A, CN112159647A, U.S. Patent US20230332010A1, etc., mostly adopt a two-component or multi-component design. The main reason is that the current coating materials generally adopt a cross-linking reaction type design, in which two or more substances react after mixing. Therefore, physical separation is required during the production and storage process. After mixing according to the proportion during use, a series of cross-linking and curing reactions occur on the surface of the protected workpiece, accompanied by the volatilization of the solvent used, to complete the formation of the coating film material. Among them, firstly, the reactive two-component design limits the storage time of the mixed materials. Generally, the suitable process time of the mixed materials is determined by the life in the tank. Obviously, this puts forward certain restrictions or requirements on the process design and process level of the process personnel in the molding stage; secondly, the molding process of this type of coating film material is relatively complicated, generally consisting of the gradual increase in the degree of curing of the resin component and the decrease in the solvent content inside the film, and the latter can also have a certain impact on the former. Generally, as the content of the solvent gradually decreases, the concentration of the reaction component in the component increases and the reaction rate will gradually increase. Since the reaction degree and the elimination of the solvent from the system proceed at the same time but at different speeds, it will inevitably bring internal stress to the cross-linked system, which is manifested in the uneven film thickness in the macroscopic way, and even causes the fine surface of the workpiece to be damaged due to the stress and strain of the film material. These are consistent with several key issues and limitations raised by the above-mentioned existing process technicians.

[0004] The technology disclosed in US Patent No. US11491255B2 and others proposed the concept and preparation idea of ​​"gel composition", attempting to solve the stress and strain problems that occur during the film forming process by reducing the modulus of the film material after curing. The technical idea is similar to that of SYLGARD™ 527 two-component addition-type silicone gel material of Dow Corning, USA, and only differs in the selection of raw materials. In actual production practice, gel materials can indeed reduce the stress formed in the molding process of a part of the film material, but due to the limitation of the composition of the two-component reactive material, it cannot completely solve the molding stress problem. At the same time, since the shape of the gel material is mainly maintained by weak physical cross-linking, the weak physical cross-linking between the longer molecular chains cannot form a good environmental barrier. Therefore, in the actual production process, the protective performance of this material is limited.

[0005] The technology disclosed in US Patent US20230332010A1 and others has proposed further improvements to the gel coating material, and has turned into a concept and technology with "viscous and elastic" or "non-Newtonian fluid". A smaller amount of cross-linking components is used to form a smaller proportion of chemical cross-linking, which further reduces the strength, cross-linking density and degree of physical cross-linking of the coating, and further improves the internal stress in the film-forming stage. However, as mentioned above, the environmental barrier capacity of the formed coating material itself is further weakened.

[0006] The technologies disclosed in U.S. Patents US20170086312A1, US20160355691A1, etc. use different materials to protect the substrate, or use multiple layers of different materials to protect the same substrate. As mentioned above, they do not solve the problems currently faced by the industry from the key perspective of the molding and working principle of the laminating film material. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a single-component conformal material and a preparation method, application and application method. The main purpose is to form a conformal surface protective film material with special functions such as temperature resistance, hydrophobicity, and environmental barrier on the surfaces of various substrates. At the same time, the conformal protective film material has lower internal stress during and after the curing process, which is particularly suitable for environmental protection of the surface of workpieces with fine structures.

[0008] The present invention is implemented by providing a one-component conformal material, comprising a high temperature resistant resin and a physical crosslinking agent, wherein the high temperature resistant resin is one or more of the high temperature resistant resins satisfying the following chemical formula A or one or more of the emulsions formed by the high temperature resistant resins satisfying the following chemical formula A:

[0009] In the chemical formula (A), R1, R2, R3, R4, R5, and R6 are one or more of methyl, ethyl, propyl, phenyl, vinyl, hydrogen, hydroxy, p-tolyl, m-tolyl, and o-tolyl, preferably one or more of methyl, phenyl, and hydrogen; R7 and R8 are one or two of methyl, ethyl, propyl, methoxy, ethoxy, propoxy, hydrogen, hydroxy, aminomethyl, aminoethyl, and aminopropyl, preferably one or more of methyl, methoxy, hydrogen, and hydroxy; x, y, and m represent the number of repetitions of the corresponding units in brackets.

[0010] Specifically, the above-mentioned single-component coating material includes the following components: 30-100 parts of the high temperature resistant resin, 200-500 parts of the solvent, 50-100 parts of the physical cross-linking agent, 20-50 parts of the material functional additive, and 1-10 parts of the process performance additive.

[0011] Specifically, the viscosity of the high temperature resistant resin is 500-100000 mPa·s, preferably 1000-50000 mPa·s; the content of the high temperature resistant resin in the emulsion is 15-80%, and the solvent in the emulsion is one or more of water, methanol, ethanol, propanol, glycerin, and petroleum ether.

[0012] Specifically, when the high temperature resistant resin is one or more of the high temperature resistant resins satisfying the chemical formula (A), the solvent in the single-component conformal material is one or more of alkanes, alcohols, toluene, and xylene; The alkane is one or more linear or branched substituted alkanes having 5 to 15 carbon atoms, preferably one or more linear or branched substituted alkanes having 6 to 9 carbon atoms; Wherein, the alcohol is one or more primary, secondary, or tertiary monohydric alcohols having 1 to 10 carbon atoms, preferably one or more primary alcohols having 2 to 5 carbon atoms; When the high temperature resistant resin is one or more of the emulsions formed by high temperature resistant resins satisfying chemical formula (A), the solvent is one or more of water, methanol, ethanol, and propanol; preferably, it is a mixture of water and ethanol, and more preferably, the mass ratio of water:ethanol is 100:10~50.

[0013] Specifically, the physical crosslinking agent in the single-component conformal material is one or more of silicone resin, phenolic resin, epoxy, polyimide polytetrafluoroethylene resin, powdered cellulose, and inorganic aerogel powder. The silicone resin is formed by chemical crosslinking of one or more of the following repeating units B, C, D, and E. The molar ratio of the resin repeating units B, C, D, and E is 100:0~50:0~35:30~100:

[0014] Wherein, R9 in the silicone resin is one or more of methyl, ethyl, phenyl, hydroxyl, hydrogen, aminomethyl, aminoethyl, and aminopropyl; Preferably, the silicone resin is synthesized according to a process well known in the industry; Silicone resin is a bulk silicone resin with a three-dimensional polymer structure; The molecular weight of silicone resin is 2000~200000g / mol; The melting temperature of silicone resin is -50 to 200°C, preferably 30 to 100°C.

[0015] The particle size range of phenolic, epoxy, polyimide, polytetrafluoroethylene resin, powdered cellulose, and inorganic aerogel powder is 5 to 50 microns.

[0016] Specifically, the material functional additives in the single-component coating material include one or more of modified white carbon black, modified oxide micropowder, and spherical resin micropowder. The modified white carbon black or modified oxide micropowder is surface-modified in a solution using hydrogenated silicone oil or hydroxy silicone oil under the catalysis of a platinum catalyst. In the modification method: The hydrogen content of hydrogen-containing silicone oil is 0.05~1.6%, and the viscosity of hydrogen-containing silicone oil is less than or equal to 2000 mPa·s; The hydroxyl content of hydroxy silicone oil is 0.1-10%, and the viscosity of hydroxy silicone oil is less than or equal to 2000 mPa·s; The platinum catalyst is an alcohol or silicone oil stabilized platinum catalyst; the platinum catalyst content is 500~10000ppm; The solvent in the solution used for modification is an alkane mixture; the modification reaction time is 1 to 5 hours; The specific surface area of ​​modified silica is 100~400m 2 / g; The oxide used in the modified oxide powder includes one or more of silicon dioxide, calcium oxide, aluminum oxide, magnesium oxide, zirconium oxide, barium oxide, and zinc oxide; the particle size of the oxide powder is 0.02 to 200 microns, preferably 0.05 to 10 microns; The oxide micropowder used in the modified oxide micropowder is spherical powder; The spherical resin powder is made of commercial resin by a two-step ball milling-solution method, and the resin includes one or more of MK, PMS MK, 610, 601, 602, 603, 604, H44, SY300, IC836, REN168, and LIOSIL eco MQ803 under the Wacker SILRES series; the resin used for the spherical resin powder also includes one or more of polytetrafluoroethylene, styrene butadiene resin and its hydrogenated resin, styrene isoprene resin and its hydrogenated resin, polyurethane, polyurea, ethylene vinyl acetate resin, ethylene methyl acrylate resin, and ethylene butyl acrylate resin.

[0017] The solution in the spherical resin powder spheroidization process is an alkane; preferably an alkane with a carbon number of 5 to 20; The particle size of spherical resin powder is 10~200 microns; The heating temperature of the ball milling-solution two-step method for spherical resin micropowder is not higher than 90°C; Preferably, the mass ratio of modified white carbon black: modified oxide micropowder: spherical resin micropowder is 0-20: 0-50: 0-35, preferably 2-10: 2-15: 5-25; Specifically, the material functional additive further includes one or more of borate esters, phosphate esters, and titanate ester small molecule compounds, and one or more of small molecule compounds satisfying the following chemical formula (F) or chemical formula (G):

[0018] Among them, R 10 is one or more of hydrogen, methyl, ethyl, propyl, group H, group I, group J, R 11 With R 12 is one or more of hydrogen, methyl, ethyl, propyl, phenyl, tolyl, R 13 With R 14 It is one or more of hydrogen, methyl, ethyl, propyl, phenyl, tolyl, methoxymethyl, and ethoxymethyl. The chemical formula of group H, group I, and group J is:

[0019] The small molecule compound of chemical formula (F) or chemical formula (G) is connected by the dotted lines in group H, group I, and group J; The carbon number of the ester group in small molecular compounds such as borate ester, phosphate ester, and titanate ester is 2 to 5; Preferably, in the material functional additive, the mass ratio of powder to small molecule compound is 100:0.01-0.1, preferably 100:0.05-0.08; Specifically, the process performance additive in the single-component coating material is one or more of a defoaming agent, a substrate wetting agent, and a bactericide; Among them, the mass ratio of defoamer: substrate wetting agent: bactericide is 1~15:0~5:0~10; The defoamer is a commercially available organosilicon-modified defoamer; the substrate wetting agent is a commercially available non-ionic substrate wetting agent; and the bactericide is a commercially available in-tank bactericide.

[0020] The present invention also provides a method for preparing a single-component conformal material. Based on the above-mentioned single-component conformal material, the preparation method comprises the following contents: adding a high temperature resistant resin, a solvent, a physical cross-linking agent, a material functional additive, and a process performance additive in portions into a sealed tank with a stirring and dispersing function, and filtering at room temperature or after heating and dispersing for 10 to 60 minutes to obtain the single-component conformal material; Among them: the sealed tank body has cooling or heating function; stirring and dispersing comes from low-speed stirring devices such as paddle type and frame type, and tooth-type high-speed dispersing device; filtering is carried out using a filter mesh; the filter mesh preferably uses a mesh number of 100-500, and a non-metallic filter mesh is preferably used.

[0021] The present invention also provides an application of a single-component conformal material, which is used for conforming the surface of a workpiece based on the single-component conformal material.

[0022] The present invention also provides an application method of a single-component conformal material. Based on the above single-component conformal material, the application method comprises the following steps repeated at least once: the single-component conformal material is shaken and applied to the surface of a workpiece to form a wet film, and then solidified at room temperature to form a conformal dry film on the surface of the workpiece; the thickness of the wet film is 10 to 200 microns; When multiple applications are required, the previous wet film must be dry before the application. The dry film thickness is 5~200 microns. When repair or removal is required after curing, a solvent is used for removal; the solvents for repair or removal include alcohols, alkanes, phenyl solvents and other commonly used industrial solvents.

[0023] Compared with the prior art, the advantages of the present invention are: The conformal material used in the present invention refers to a material that uses a liquid with good fluidity through certain means to form a film of uniform thickness on the surface of a workpiece with a complex shape. The characteristic is that it does not require complex and time-consuming molding processes. By utilizing the characteristics of the material itself, it can form a film in situ on the surface of workpieces of various materials and with various heights and depths. This is quite different from the existing film materials that are attached to the surface of the substrate through technical means, or formed by means of vapor deposition and other means.

[0024] The conformal material disclosed in the present invention can form a film material with uniform thickness on a vertical surface including the surface of a workpiece, and conformal material practitioners do not need to make complicated process adjustments according to the surface of the workpiece.

[0025] The conformal material disclosed in the present invention is suitable for the surface protection of various types of workpieces. In terms of the type of workpiece material, the conformal material disclosed is suitable for various types of substrates including plastics, metals, inorganic materials, etc. In terms of the type of workpiece, the conformal material disclosed is suitable for the protection of various types of workpieces such as mechanical equipment, medical equipment, electronic circuits, etc., among which it is particularly suitable for the surface protection of workpieces with fine and complex structures on the surface. At the same time, the conformal material disclosed in the present invention can also be used in combination with other surface protection materials. For example, a conformal protective film is formed on the surface of a lightweight alloy workpiece constructed with a special marine anti-corrosion coating system, providing the existing coating system with hydrophobic, high temperature resistant, insulating and anti-breakdown properties, which can effectively extend the environmental protection effect of the underlying coating. For example, the conformal material is formed on the surface of a sensor coil that has been constructed with insulating material and wound, which can effectively improve the comprehensive performance of the underlying insulating material and maintain stable performance at higher ambient temperatures.

[0026] The single-component coating material disclosed in the present invention adopts relatively strong physical crosslinking as the main molding mechanism. The formed coating material does not undergo obvious chemical crosslinking, but instead achieves molding and protection effects through sufficient and effective physical crosslinking. The physical crosslinking inside the formed coating film has good heat resistance and self-healing effects, and more importantly, the formed physical crosslinking process is not related to the solution concentration inside the film, and will not bring additional stress and strain to the inside of the film during the molding process. Therefore, the single-component coating material disclosed in the present invention, the application process of the coating material, and the surface coating protective film material formed therefrom overcome the defects of existing coating materials.

[0027] The cladding material disclosed in the present invention has good universal applicability. Its single-component, heat-resistant, insulating and other properties, as well as good construction and repair properties, make it universally applicable in many industries. DETAILED DESCRIPTION

[0028] The specific implementation method disclosed in the present invention is only one application mode of the one-component conformal material disclosed in the present invention, and does not limit the present invention in any other forms. Using the one-component conformal material disclosed in the present invention, industry insiders can apply it in a variety of environments and working conditions.

[0029] The high temperature resistant resin disclosed in the present invention has obvious significance for the normal operation of the coating material. In production practice, when and only when the resin component satisfying the chemical formula A is used, the obtained coating material can have good heat resistance. When the types of groups in the chemical formula A are different, the working temperature range of the coating material is 100~250℃, which is significantly higher than most existing coating materials. In addition, since the high temperature resistant resin component is relatively single, the physical, mechanical and electrical properties of the coating material are relatively stable under long-term working environment, which is significantly better than some commercially available high temperature resistant coating materials. Taking an existing silicone rubber-based high temperature resistant coating material as an example, at an operating temperature of 180℃, the coating material will release some white mist gas in the early stage at this temperature. After stabilization, the Shore hardness, tensile strength, elongation at break, and protective performance of the coating material will show obvious loss. Under certain specific conditions, the coating material after high temperature treatment will also fall off, yellow, become brittle, and powderize. The reason for this phenomenon is that the raw materials used are a mixture of polymers of various molecular weights, some of which contain low molecular weight components that have a certain flexibility effect. They have a low heat resistance temperature, are volatile, and are easy to decompose. After these components volatilize or oxidize under high temperature conditions, they can significantly affect the performance of the overall conformal material. For certain closed application environments, such as in spacecraft or near optical components, the thermal decomposition products produced by this conformal material can further condense at the cold end, thereby significantly affecting the normal operation of the overall equipment. The high temperature resistant resin used in the present invention can effectively avoid the occurrence of this phenomenon.

[0030] Full use of physical crosslinking is one of the key factors for the good effect of the present invention. In the coating material, especially the coating material with high temperature resistance, the physical crosslinking mechanism of the present invention has a special advantage of reversibility compared with the existing coating material technology that relies on chemical crosslinking. Physical crosslinking has good reversible characteristics, which is similar to the reversible hydrogen bond inside the polyurethane resin, but has better thermal stability than hydrogen bond. The physical crosslinking that occurs in the coating material of the present invention is caused by the joint action of similar functional groups and the special structure of the physical crosslinking agent itself. Compared with other types of additives and fillers, having similar or identical functional groups helps the physical crosslinking agent of the present invention to be fully dispersed with the high temperature resistant resin, effectively promotes the enrichment and arrangement of the molecular chain of the high temperature resistant resin near the physical crosslinking agent, and even induces the local crystallization, which can be observed under an optical microscope equipped with a polarized lens. Compared with the chemical crosslinking commonly used in the existing high temperature resistant coating materials, the concept of physical crosslinking is not affected by the content, position and distribution of the reactive groups in the continuous phase resin, but is evenly dispersed in the continuous phase through its own good compatibility, thereby achieving a better crosslinking effect. This is also one of the important factors that make the coating material of the present invention have better environmental protection performance. From the perspective of temperature resistance, there is no chemical bond between the physical crosslinking agent and the surrounding continuous phase high temperature resistant resin during the physical crosslinking process, and it is not limited by the different decomposition temperatures due to different types of chemical bonds. In addition, physical crosslinking, similar to hydrogen bonding, also has effective self-recovery properties. Under extreme temperatures, after the temporary failure of physical crosslinking caused by the melting of high temperature resistant resin or physical crosslinking agent, as the ambient temperature decreases, physical crosslinking can take effect again in the coating material.

[0031] In addition, as mentioned above, the process of physical cross-linking is different from chemical reaction, and is not significantly affected by its own concentration, and can rearrange itself within a larger range. This means that the technical means adopted by the present invention basically overcomes the phenomenon of internal stress that occurs during and after the curing process of most existing coating materials. For example, the internal stress of the coating material disclosed in the present invention is not affected by the solvent content inside the coating film, and as the solvent evaporates, the stress inside the coating material of the present invention does not change significantly. Of course, the above description does not rule out the possibility that no chemical cross-linking reaction occurs in the coating material at all, but only illustrates that the phenomenon of physical cross-linking is the main factor that affects the coating material in the present invention.

[0032] The spherical resin powder described in the present invention is an important hydrophobic functional additive. Within a certain temperature range, some types of resins can be self-assembled in a specific solvent and at a certain stirring speed to obtain a spherical powder material with good sphericity after grinding. This is related to the surface energy difference generated by the interaction between the resin and the surrounding environment under a specific environment.

[0033] In order to further verify the comprehensive performance of the cladding material disclosed in the present invention, the cladding materials prepared in the following three embodiments were formed on the surfaces of three different substrates, namely, pure copper plate (Example 1), tinplate plate (Example 2) and circuit test board (Example 3) by airless spraying or brushing, and four tests of temperature resistance, electrical strength, neutral and acidic salt spray were carried out in turn. The conditions of the films formed by the cladding materials and the test results are shown in Table 1. Among them, the temperature resistance test method is to observe the coating state after placing the sample on a 200°C heating platform for 24 hours; the electrical strength test is carried out in accordance with the standard GB / T 1408.2-2016; and the salt spray test is carried out in accordance with GJB150.11A-2009.

[0034] Table 1 Examples 1 to 3 and some of their properties project Example 1 Example 2 Example 3 Substrate Pure copper plate Tinplate Circuit test board Molding process Airless spray Brush Selective spraying Wet film thickness 150~200 microns 50~100 microns 50~100 microns Drying time 15min 30min 5min Dry film thickness 30~50 microns 20~30 microns 20~30 microns Heat resistance No change No change No change Electrical strength ≥45kV / mm ≥40kV / mm ≥47kV / mm Neutral salt spray 9000h no change 5000h no change 8000h no change Acidic salt spray 5000h no change 4000h no change 7000h no change

[0035] Example 1

[0036] 100g of AEROSIL® 200 white carbon black, 5g of hydrogen-containing silicone oil with a hydrogen content of 0.6%, and 0.05g of a 10000ppm platinum catalyst stabilized by vinyl silicone oil were dispersed at high speed in 2000g of n-hexane for 2h, and then filtered and dried to obtain surface-treated modified white carbon black. 250g of silicon dioxide particles with a particle size of 10 microns, 5g of hydrogen-containing silicone oil with a hydrogen content of 0.35%, and 0.05g of a platinum catalyst stabilized by vinyl silicone oil with a content of 5000ppm were dispersed at high speed in 2000g of n-hexane for 5h, and then filtered and dried to obtain surface-treated modified oxide micropowder. 35g of high temperature resistant resin K with a viscosity of 7500 mPa·s, 175 of xylene, 125 of n-heptane, 40g of silicone resin with a molar ratio of silicone repeating units B:C:D:E of 10:2.5:3.5:7, 20g of polyimide powder with a particle size of 10 μm, 5g of the above-mentioned modified white carbon black, 20g of the above-mentioned modified oxide powder, 0.01g of compound L, 0.01g of tetra-n-butyl titanate, 0.95g of defoaming agent DF-2471 (Defeng), 1.0g of wetting agent TEGO 432 (Di Gao), and 0.05g of bactericide (Sanyu Chemical) were put into a closed dispersion container, and a frame-type stirring paddle was turned on to disperse at a speed of 500 rpm for 15 minutes, and then heated to 55°C, and then a high-speed dispersion disk was turned on to disperse at 3000 rpm for 60 minutes, and filtered through a 400-mesh screen to obtain a coating material. The conformal material was sprayed on the surface of the pure copper plate 4 times by airless spraying, with an interval of 5 minutes between each spray. The conformal material sample was obtained after curing at room temperature for 15 minutes.

[0037] Example 2

[0038] 75 g SILRES MK, 25 g SILRES 610, 40 g LIOSIL eco MQ 803 and 10 g polytetrafluoroethylene powder were crushed and sieved, dispersed in 1000 g cyclohexane at high speed and slowly heated to 80°C for reflux. After dispersing for 30 minutes, the heating was turned off and the dispersion was continued. After naturally cooling to room temperature, the spherical resin powder was filtered and dried. 75g of 55% aqueous emulsion of high temperature resistant resin M (viscosity of about 10000 mPa·s), 250g of water, 120g of ethanol, 30g of propanol, 75g of silicone resin with a molar ratio of silicone repeating units B:C:D:E of 10:0:2.5:9.5, 25g of the above-mentioned spherical resin powder, 0.02g of compound N, 1.0g of defoamer (Meiyu Chemical), and 1.0g of wetting agent (Silok 7145, Silok) were put into a closed dispersion container, and the frame-type stirring paddle was turned on to disperse at a speed of 500 rpm for 15min, and then heated to 50°C, and then the high-speed dispersion disk was turned on to disperse at 3000 rpm for 45min, and filtered through a 300-mesh screen to obtain a conforming material. The conforming material was applied to the surface of the tinplate three times by brushing, with an interval of 10 minutes between each pass, and the conforming material sample was obtained after curing at room temperature for 30 minutes.

[0039] Example 3

[0040] 2000g of alumina powder with a particle size of 0.05 micron, 50g of hydroxy silicone oil with a hydrogen content of 0.75%, and 5g of platinum catalyst with a stable content of 3000ppm of vinyl silicone oil were dispersed in 8000g of n-hexane at high speed for 5 hours, and then filtered and dried to obtain surface-treated modified oxide powder. 85g of high temperature resistant resin O with a viscosity of 1250 mPa·s, 250g of cyclopentane, 50g of cyclohexane, 70g of xylene, 30g of heptane, 90g of silicone resin with a molar ratio of silicone repeating units B:C:D:E of 100:15:0:85, 15g of modified white carbon black in Example 1, 25g of the above surface treated modified oxide powder, 0.023g of compound P, 0.02g of triethyl borate, 0.4 of defoamer, and 0.6g of bactericide were placed in a closed dispersion container, and the frame-type stirring paddle was turned on to disperse at a speed of 200 rpm for 30min, heated to 60°C, and the high-speed dispersion disk was turned on to disperse at 6000 rpm for 30min, and filtered through a 500-mesh screen to obtain a conformal material. The conformal material was applied to the comb-shaped electrode part of the circuit test board 4 times by automatic selective spraying, with an interval of 1 minute between each time, and the conformal material sample was obtained after curing at room temperature for 5 minutes.

[0041] The preparation and application process of the one-component hydrophobic silicone coating material described above is only an example of a preferred embodiment of the present invention, and does not limit the present invention in any way. Any person skilled in the art may use the disclosed technical content to change or modify it into an equivalent implementation example with equivalent changes. However, any simple modification, equivalent change and modification made to the implementation example based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A single-component conformal material, characterized in that: It comprises a high temperature resistant resin and a physical cross-linking agent, wherein the high temperature resistant resin is one or more of the high temperature resistant resins satisfying the following chemical formula A or one or more of the emulsions formed by the high temperature resistant resins satisfying the following chemical formula A: ; In the chemical formula (A), R1, R2, R3, R4, R5, and R6 are one or more of methyl, ethyl, propyl, phenyl, vinyl, hydrogen, hydroxy, p-tolyl, m-tolyl, and o-tolyl; R7 and R8 are one or two of methyl, ethyl, propyl, methoxy, ethoxy, propoxy, hydrogen, hydroxy, aminomethyl, aminoethyl, and aminopropyl; and x, y, and m represent the number of repetitions of the corresponding units in the brackets.

2. The single-component conformal material according to claim 1, characterized in that: The invention comprises the following components: 30 to 100 parts of the high temperature resistant resin, 200 to 500 parts of the solvent, 50 to 100 parts of the physical cross-linking agent, 20 to 50 parts of the material functional additive, and 1 to 10 parts of the process performance additive.

3. The single-component conformal material according to claim 2, characterized in that: The viscosity of the high temperature resistant resin is 500-100000 mPa·s; the content of the high temperature resistant resin in the emulsion is 15-80%.

4. The single-component conformal material according to claim 2, characterized in that: When the high temperature resistant resin is one or more of the high temperature resistant resins satisfying chemical formula (A), the solvent is one or more of alkanes, alcohols, toluene, and xylene; when the high temperature resistant resin is one or more of the emulsions formed by the high temperature resistant resins satisfying chemical formula (A), the solvent is one or more of water, methanol, ethanol, and propanol.

5. The single-component conformal material according to claim 2, characterized in that: The physical crosslinking agent is one or more of silicone resin, phenolic resin, epoxy, polyimide polytetrafluoroethylene resin, powdered cellulose, and inorganic aerogel powder. The silicone resin is formed by chemical crosslinking through one or more of the following repeating units B, C, D, and E: ; Among them, R9 in the silicone resin is one or more of methyl, ethyl, phenyl, hydroxyl, hydrogen, aminomethyl, aminoethyl, and aminopropyl.

6. The single-component conformal material according to claim 2, characterized in that: The material functional additives include one or more of modified white carbon black, modified oxide micropowder, and spherical resin micropowder. The modified white carbon black or modified oxide micropowder is surface-modified in a solution using hydrogenated silicone oil or hydroxy silicone oil under the catalysis of a platinum catalyst; the process performance additives are one or more of a defoaming agent, a substrate wetting agent, and a bactericide.

7. The single-component conformal material according to claim 6, characterized in that: The material functional additives also include one or more of borate esters, phosphate esters, and titanate ester small molecule compounds, and one or more of small molecule compounds satisfying the following chemical formula (F) or chemical formula (G): ; Among them, R 10 is one or more of hydrogen, methyl, ethyl, propyl, group H, group I, group J, R 11 With R 12 is one or more of hydrogen, methyl, ethyl, propyl, phenyl, tolyl, R 13 With R 14 It is one or more of hydrogen, methyl, ethyl, propyl, phenyl, tolyl, methoxymethyl, and ethoxymethyl. The chemical formula of group H, group I, and group J is: ; The small molecule compound of the chemical formula (F) or the chemical formula (G) is connected by the dotted lines in the group H, the group I, and the group J.

8. A method for preparing a single-component conformal material, characterized in that: Based on the single-component conformal material described in any one of claims 2 to 7, the preparation method comprises the following contents: adding high temperature resistant resin, solvent, physical crosslinking agent, material functional additive, and process performance additive in portions into a sealed tank with stirring and dispersing function, and filtering at room temperature or after heating and dispersing for 10 to 60 minutes to obtain the single-component conformal material.

9. An application of a single-component conformal material, characterized in that: The single-component conformal material according to any one of claims 1 to 7 is used for conforming the surface of a workpiece.

10. A method for applying a single-component conformal material, characterized in that: Based on the single-component conformal material described in any one of claims 1 to 7, the application method includes repeating the following content at least once: shaking the single-component conformal material and applying it to the surface of the workpiece to form a wet film, and forming a conformal dry film on the surface of the workpiece after curing at room temperature; the thickness of the wet film is 10 to 200 microns.

Citation Information

Patent Citations

  • Silicone-type coatings and preparation method thereof

    CN101805562B

  • Organosilicon coating and preparation method thereof

    CN102559047B

  • Antistatic organosilicon gel used for heat-conducting gasket and preparation method of the organosilicon gel

    CN103613931A

  • An organosilicon coating adhesive and its preparation method

    CN103666250B

  • Two-component encapsulating adhesive, its preparation method, usage method and application

    CN108913089B

Cited By

  • Single-component conformal material, and preparation method, use, and use method

    WO2026170861A1